Wykluczenie społeczne a ubóstwo w społeczeństwie - Sempryk, Jarosław (Społeczeństwo, 2022)
The aim of the article is to draw attention to the issue of poverty. This issue is very complex. Social exclusion is part of the functioning of capitalist democracy in the overpopulated and multicultural societies. Material exclusions are mainly the result of a lack of work. Therefore, access to it is, according to many philosophers and economists, a basic condition. The negative effect of globalization are socioeconomic inequalities, which arise as a result of departing from the principle of social justice. In contemporary conditions resulting directly from the globalization process, the source of the solution to the indicated socioeconomic problem may be broadly understood system education, provided that the education system is well managed.